Altered peripheral B lymphocyte homeostasis and functions mediated by IL-27 via activating the mammalian target of rapamycin signaling pathway in patients with rheumatoid arthritis. (5th October 2021) - Tang, Yawei; Bai, Ziran; Qi, Jingjing; Lu, Zhimin, Ahmad; Wang, Guan; Jin, Minli; Wang, Bing; Chen, Haifeng; Li, Xia
Abstract: B cell dysfunction and inflammatory cytokine over-production participate in the pathogenesis of rheumatoid arthritis (RA). Here we compared peripheral B cell homeostasis and immune functions between RA patients and healthy controls (HC) and explored vital signaling pathways involved in altered RA B cells. We found that RA patients showed significantly decreased frequencies of peripheral CD19 + CD27 + CD24 high regulatory B (Breg) cells but increased frequencies of CD19 + CD27 + CD38 high plasmablasts and CD19 + CD138 + plasma cells, and higher levels of serum immunoglobulin (Ig)M and IgG. Compared to HC peripheral B cells, RA peripheral B cells had more increased proliferation and higher expression of activation markers. Importantly, our results showed that RA peripheral B cells displayed the mTOR signaling pathway to be more activated, and inhibition of mTOR could restore RA B cell homeostasis and functions. RA serum-treated B cells exhibited more increased expressions of mTOR, which could be restored with the addition of anti-interleukin (IL)-27 neutralizing antibody. Serum IL-27 levels were significantly increased in RA patients and positively correlated with disease activity, the frequencies of plasma cells and the levels of autoantibodies. In vitro, IL-27 notably promoted immune dysfunction of RA B cells, which were inhibited by anti-IL-27 neutralizing antibody. Also, the mTOR pathway was more activated in IL-27-treated RA B cells, and mTOR inhibition apparently reversed abnormalities of RA B cells mediated by IL-27. These results suggest that increased serum IL-27 levels could promote peripheral B cell dysfunction in RA patients via activating the mTOR signaling pathway. Thus, IL-27 may play a pro-pathogenic role in the development of RA, and antagonizing IL-27 could be a novel therapy strategy for RA. Graphical Abstract: